2021
DOI: 10.1177/0165025420981642
|View full text |Cite
|
Sign up to set email alerts
|

Global perspectives on physical and nonphysical discipline: A Bayesian multilevel analysis

Abstract: Background and Objective: Sixty countries worldwide have banned the use of physical punishment, yet little is known about the association of physical and nonphysical forms of child discipline with child development in a global context. The objective of this study is to examine whether physical punishment and nonphysical discipline are associated with child socioemotional functioning in a global sample of families from 62 countries and whether country-level normativeness of physical punishment and nonphysical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 21 publications
3
18
0
Order By: Relevance
“…It also is remarkably similar to the association between corporal punishment and young Colombian children's cognitive skills assessed using LDV and matching methods, which ranged from −.08 to −.21 SD (Cuartas et al, 2020). These results align with past studies showing negative links between spanking and selected SE‐related skills like getting along well with other children in LMICs (Grogan‐Kaylor et al, 2021; Pace et al, 2019), and reached similar conclusions by employing a comprehensive measure that considered the dimensionality of SE skills. Because SE skills are fundamental for children's success in academic and social settings for children to manage stress, attend and process information, and maintain positive relationships (Jones & Bouffard, 2012; Liew, 2012), the current findings and those from past studies collectively suggest that spanking might be detrimental for young children's development and wellbeing.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…It also is remarkably similar to the association between corporal punishment and young Colombian children's cognitive skills assessed using LDV and matching methods, which ranged from −.08 to −.21 SD (Cuartas et al, 2020). These results align with past studies showing negative links between spanking and selected SE‐related skills like getting along well with other children in LMICs (Grogan‐Kaylor et al, 2021; Pace et al, 2019), and reached similar conclusions by employing a comprehensive measure that considered the dimensionality of SE skills. Because SE skills are fundamental for children's success in academic and social settings for children to manage stress, attend and process information, and maintain positive relationships (Jones & Bouffard, 2012; Liew, 2012), the current findings and those from past studies collectively suggest that spanking might be detrimental for young children's development and wellbeing.…”
Section: Discussionsupporting
confidence: 90%
“…Spanking remains normative in several countries across the globe (Global Initiative to End Corporal Punishment of Children, 2021), and some conceptual frameworks suggest that the developmental consequences of spanking might differ according to its social normativeness (Deater‐Deckard & Dodge, 1997). Yet, the literature from LMICs shows consistent associations between spanking and detrimental child outcomes, including hitting other children and being easily distracted (Grogan‐Kaylor et al, 2021; Pace et al, 2019), internalizing problems (Xing & Wang, 2013), externalizing behaviors (Xing & Wang, 2013), and slower cognitive growth (Cuartas et al, 2020). While I could not directly test whether the normativeness of spanking moderated its association with SE skills, the current findings show that spanking might lead to detrimental SE outcomes in Bhutan.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, physical punishment was found to associate with Externalizing Problems. Similar findings have been reported by several international studies [ 62 ]. A meta-analysis of a sample of 292 middle-class families with 8–12 years-old children from several countries (China, India, Italy, Kenya, Philippines and Thailand), found that physical punishment which included spanking, slapping, grabbing, shaking, and beating up, was associated with adverse child outcomes [ 38 ].…”
Section: Discussionsupporting
confidence: 93%